Epistemological Beliefs Of The Educator And The Learners In A Dialogic Teaching And Learning Context In Malaysian Higher Education - Shaari, Anis (2013)
Education has always been an integral part in an individual’s life and in a nation’s survival, at large. Being equated to the process of teaching and learning, it is always expected to meet the demands of many parties including the community, the educational institution itself and the country. As for a higher learning milieu, the teaching and learning process is enlightened with various methodologies in lesson delivery. Among all, dialogic teaching and learning is found to be a suitable pedagogical method which offers a great deal of benefits. An educator was identified to practice such a method and it was one of the objectives of this research to uncover the practice in a Malaysian tertiary education context. Besides, the study was also conducted to explore the epistemological beliefs both the educator and her learners hold within the dialogic process. Employing a fully qualitative approach, the research generally implicated an educator and 41 learners of whom were directly involved in the dialogic teaching and learning. In particular, all the 41 learners agreed to be observed and they also shared their views pertaining to the dialogic practice through a series of journal entries. However, only seven of them, together with the educator were interviewed. From the three data gathering procedures, thematic data analysis was used. The results, from the educator’s perspective, generally demonstrated that the dialogue was a practice of belief in which it rejects the idea of transmissionary view of teaching and learning. In other words, the educator was found to conform to Freire’s (1970, 1997) notion which propagates the idea of equality of roles in a teaching and learning process. As for the learners, it could be concluded that the practice of dialogue was still not pervasive enough, despite the similar belief they held in comparison with the educator’s. The learners could be said to theoretically approve the philosophy underlying the dialogic approach yet not to fully practically exercise such beliefs. The findings, thus, suggested a number of pedagogical implications and invited several recommendations for future research as well as practice.